2018
DOI: 10.1093/molehr/gay013
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of mTOR, PPARγ and PPARδ signaling in regulating early pregnancy decidual function, embryo viability and feto-placental growth

Abstract: Funding was provided by the Agencia Nacional de Promoción Científica y Tecnológica de Argentina (PICT 2014-411 and PICT 2015-0130), and by the International Cooperation (Grants CONICET-NIH-2014 and CONICET-NIH-2017) to A.J. and T.J. The authors have no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 59 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…PPARγ, a downstream regulator of FPR2, is a member of nuclear receptor transcription factor superfamily and is involved in a variety of physiological and pathological processes such as lipid and glucose metabolism, energy homeostasis, inflammation, cell proliferation and differentiation. The previous study revealed that PPARγ was involved in the invasion and differentiation of trophoblasts 41 and played an important role in embryo implantation, placenta formation and trophoblast differentiation and maturation. PPARγ can also inhibit inflammation by entering the nucleus, following binding to NF‐κBp65 and inhibiting its transcriptional activity 42 .…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ, a downstream regulator of FPR2, is a member of nuclear receptor transcription factor superfamily and is involved in a variety of physiological and pathological processes such as lipid and glucose metabolism, energy homeostasis, inflammation, cell proliferation and differentiation. The previous study revealed that PPARγ was involved in the invasion and differentiation of trophoblasts 41 and played an important role in embryo implantation, placenta formation and trophoblast differentiation and maturation. PPARγ can also inhibit inflammation by entering the nucleus, following binding to NF‐κBp65 and inhibiting its transcriptional activity 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PPARδ and its role during the peri-implantation period was also documented in the ovine trophoblast [ 32 ]. In addition, Roberti et al [ 33 ] suggested that PPARδ was the key factor in post-implantation development, preventing embryo resorption. Taking the above into consideration, the presence of PPARs seems to be essential during bovine embryo development, but mechanisms of their regulatory function need to be proven in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…To perform immunostaining for CTGF and MMP2, placental tissues were fixed in buffered formaldehyde solution 4% v/v, then paraffinized and serially cut into 5 μm thick sections. Then, as previously, sections were deparaffinized, rehydrated through a graded series of ethanol and the endogenous peroxidase activity was blocked. The sections were processed using the corresponding primary antibodies: anti‐CTGF (goat polyclonal antibody, 1:300 dilution, Santa Cruz Biotechnology), and anti‐MMP2 (mouse polyclonal antibody, 1:200 dilution, Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%